Mainstreaming microfinance : how lending to the poor began, grew, and came of age in Bolivia - Rhyne, Elisabeth (Bloomfield, CT : Kumarian Press, 2001)
This book provides a very important contribution to debates surrounding microfinance as a commercial proposition and as a means of empowering the entrepreneurial poor..
Includes bibliographical references and index.
aug 03/05/13, ijb 26/02/2019
Loans
Keywords: Microfinance -Bolivia